The County Court of Ćuprija in 1840s: А Contributions to History - Popović, Miroslav M. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The aim of the paper before us is to present the basic features of the development of the County Court of Ćuprija in the 1840s, its organization and work, based on the report of the Ministry of Justice, which contain statistical data and conduit lists with information about employees. The paper is also based on published documents of the Court, schematism and the Census of Tax Heads, Municipalities and Conciliation Courts in the Principality of Serbia from 1839.The County Court of Ćuprija took its place in the network of county courts of the Principality of Serbia, which was the basis of the judicial system, which, after the Constitution of 1838, the first regulations, decrees and laws on organization and procedure, made its first serious steps. When it comes to staff, the members of the court were people with experience, most of the employees had completed normal schools, therefore, they had basic preconditions for performing the service. The Commission for the Improvement of Civil Procedure from 1845 found that the Ćuprija court also entered the group of overburdened, and increased its staff by one clerk. When looking at official data, the number of crimes and civil lawsuits at the Ćuprija County Court increased during the 1840s, especially in 1845 the court had problems with accumulated civil lawsuits. There was a drastic increase in adjudicated cases of crimes and lawsuits after 1845, and it seems that the interventions of state authorities have influenced the increase of efficiency, and, perhaps, the trend of adopting new, more differentiated, applicable, clearer and more efficient regulations, both in the field of judicial organization and various branches of civil and criminal law and court procedure.
Keywords: Principality of Serbia; judiciary; statistics; County Court of Ćuprija